Polyimide enameled wire and preparation method thereof
By dispersing rice-shaped hafnium dioxide nanoparticles in the coating of polyimide enameled wire, the problem of insufficient thermal stability of polyimide enameled wire in high temperature environments is solved, and higher heat resistance and insulation properties are achieved. , suitable for miniaturization, high power, and high voltage applications.
Patent Information
- Application Number
- CN202411716693.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-27
AI Technical Summary
When used in high-temperature environments, the existing polyimide enameled wire has insufficient heat resistance and stability, which cannot meet the needs of miniaturization, high power, and high voltage application scenarios.
By uniformly dispersing rice-shaped hafnium dioxide nanoparticles in the polyimide coating, polyimide enameled wires with higher initial decomposition temperatures were prepared. The method includes preparing rice-shaped hafnium dioxide nanoparticles, adding them to a polyamic acid solution, and solidifying them by heating to form a coating.
Significantly improves the heat resistance of polyimide enameled wire, extends its service life, and maintains long-term thermal stability at higher temperatures while enhancing insulation performance and mechanical strength.
Smart Images

Figure CN119331507A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of enameled wires, and in particular to a polyimide enameled wire and a preparation method thereof. Background Art
[0002] Enameled wire is an important component of electrical equipment. Its structure is a core-to-core structure with a metal conductor as the inner core and an insulating coating as the outer skin. Enameled wire is widely used in motors, electrical appliances, inductors, transformers and household appliances. With the development of the times and the advancement of science and technology, higher requirements are placed on the temperature resistance of enameled wire during use. The performance of enameled wire depends largely on the quality and performance of the enameled wire paint film. The ideal enameled wire paint film should have good insulation, high temperature resistance, low temperature resistance, chemical corrosion resistance, certain mechanical strength and good adhesion to the wire. At present, the types of enameled wire paint films mainly include polyurethane, polyester, polyimide, polyamide-imide and composite coating enameled wire paint. Among them, polyimide enameled wire paint is the insulating paint with the highest temperature resistance among enameled wires, and the long-term use temperature can reach above 220°C.
[0003] Although traditional polyimide enameled wire has good heat resistance and insulation performance, it still has deficiencies in some special applications, such as electronic equipment under high temperature environment. In order to improve the heat resistance and insulation performance of polyimide enameled wire, oxides or heat-conducting fillers, such as aluminum oxide, graphene, etc., are often added to polyimide materials, wherein the addition of high temperature resistant oxide particles can bear part of the load, reduce the stress of polyimide, and prevent its thermal decomposition reaction, which can effectively improve the heat resistance of polyimide and extend the service life. For example, CN111154100A discloses a method for preparing a high heat-resistant polyimide, wherein γ-aminopropyltriethoxysilane is used as a raw material to prepare a cage-shaped octapoly (γ-aminopropyl) silsesquioxane, and then a cage-shaped octapoly (γ-aminopropyl) silsesquioxane, diamine, dianhydride and other raw materials are used to prepare a modified polyimide. The unique cage structure of cage-shaped octapoly (γ-aminopropyl) silsesquioxane has excellent mechanical properties and thermodynamic stability. Introducing it into the synthetic raw materials of polyimide precursors can improve the comprehensive mechanical properties of polyimide, and improve the elastic properties and heat resistance of polyimide. CN103172859A discloses a polyamic acid dispersion and a polyimide film, including: dispersing metal oxide nanoparticles whose surfaces are modified by coupling agents into an organic solvent to obtain a nanoparticle dispersion; then mixing the obtained nanoparticle dispersion with dianhydride and diamine to react to obtain a polyamic acid dispersion. First, the surface of the metal oxide nanoparticles is modified and dispersed in an organic solvent with low viscosity, so that the nanoparticles are evenly and stably dispersed, and then a polymerization reaction is performed to prepare a polyimide film with good mechanical properties and thermal stability. The introduction of heat-conducting materials can improve the heat conduction capacity and heat dissipation efficiency. For example, CN112592653A discloses a method for preparing a high-temperature resistant polyimide wire enamel, which uses surface-modified graphene oxide and a polyimide system for compounding. Graphene oxide has an ultra-high specific surface area and a two-dimensional planar nanostructure, and has the possibility of being compounded with a polyimide system to obtain heat resistance and high mechanical properties. CN115746696A discloses a high-heat-resistant polyimide enameled wire, which uses a polyamic acid solution obtained by in-situ polycondensation of aromatic dianhydride, aromatic diamine and fluorinated amino graphene as a polyimide varnish, and thus prepares an enameled wire. The obtained enameled wire has excellent mechanical, high-temperature durability and low dielectric loss properties while maintaining excellent heat resistance.
[0004] However, as electronic equipment develops towards miniaturization, lightweight and high performance, the requirements for the heat resistance or thermal stability of enameled wires are becoming increasingly higher. Therefore, it is necessary to continue exploring polyimide enameled wires with higher heat resistance.
[0005] Hafnium dioxide (HfO2) is an important dielectric insulating material with the advantages of excellent high temperature resistance, high dielectric constant, good chemical stability, easy processing, etc. It is widely used in research. For example, CN111234529A discloses a polyimide dielectric film. The raw materials of the polyimide dielectric film include aromatic diamine compounds, aromatic tetracarboxylic dianhydride compounds and nanopowders that can be hafnium oxide. By adding wide-bandgap nanopowders to the raw materials, the prepared polyimide dielectric film can have high insulation properties and high dielectric constants, and can provide dielectric properties and electric displacement polarization of the film. In addition, the wide-bandgap nanopowders can effectively inhibit the injection of charges and the diffusion of internal charges, greatly reduce the conductivity loss under high temperature and high electric field, and significantly improve the high-temperature energy storage capacity of the material. CN116376072A discloses a hafnium dioxide modified polyimide film, which obtains hafnium dioxide powder with high dielectric, corrosion resistance and good thermal stability by a simple hydrothermal method, and uses the powder to synthesize hafnium dioxide modified polyimide enameled wire by in-situ polymerization. The initial decomposition temperature of PI is increased from 448°C to 471°C, which improves the high temperature resistance and insulation performance of the polyimide film. Although the above measures can improve the high temperature resistance of polyimide enameled wire to a certain extent, in the face of high temperature use environments in application scenarios such as miniaturization, high power, and high voltage, the heat resistance temperature increase cannot fully meet the use needs. Therefore, it is necessary to provide a polyimide enameled wire with higher heat resistance stability, which can maintain long-term thermal stability at higher temperatures. Summary of the invention
[0006] The present invention aims to overcome the deficiencies in the prior art and provide a polyimide enameled wire and a preparation method thereof, so as to solve the problem of insufficient heat resistance stability of the enameled wire in more demanding usage scenarios, and provide an enameled wire that can be used at higher temperatures, which can significantly improve the heat resistance, insulation and mechanical strength of the enameled wire.
[0007] To achieve the above-mentioned purpose of the present invention, the first aspect of the present invention provides a polyimide enameled wire, comprising a conductor and a polyimide coating arranged on the conductor, wherein rice-grain-shaped hafnium dioxide nanoparticles are uniformly dispersed in the polyimide coating, and the rice-grain-shaped refers to the shape of the hafnium dioxide particles dispersed in the SEM image.
[0008] As a preferred technical solution, the polyimide coating is formed by heating and curing a polyamic acid solution containing rice-grain-shaped hafnium dioxide nanoparticles, and the rice-grain-shaped hafnium dioxide nanoparticles are uniformly dispersed in the polyamic acid solution.
[0009] As a preferred technical solution, the average particle size of the hafnium dioxide nanoparticles is 100-150 nm, accounting for 1%-5% of the total weight of the polyimide coating.
[0010] As a preferred technical solution, the conductive wire is a copper wire or an aluminum wire, and the thickness of the polyimide coating is 0.01-0.1 mm.
[0011] As a preferred technical solution, the rice-like hafnium dioxide nanoparticles are prepared by the following method: weigh 3.22 g of HfCl4 and dissolve it in 5 ml of methanol to obtain solution A; weigh 1.51 g of CH3COONa and add it to 10 ml of methanol to obtain solution B; add solution B dropwise to solution A to obtain a mixed solution; pour the mixed solution into a 50 ml autoclave, heat it to 120°C~200°C and keep it at this temperature for 3~10 h, then wait for the autoclave to cool naturally, collect the product after centrifugal washing, and then place it in a blast drying oven at 90°C for 5 h to obtain. In the previous study, the applicant found that when hafnium dioxide is added to polyimide film, the dielectric properties of polyimide at high temperature can be improved, and the initial decomposition temperature of PI can be increased from 448°C to 471°C, which improves the thermal stability of polyimide film. However, it is still not possible to use stably for winding groups that require higher operating temperatures. In order to further improve the operating temperature range of the enameled wire, the applicant has conducted a lot of research and unexpectedly discovered that the polyimide enameled wire prepared by adding rice-like hafnium dioxide nanoparticles with a specific morphology has a higher initial decomposition temperature, which can reach 530°C. Compared with pure polyimide or polyimide enameled wire with spherical hafnium dioxide prepared by simple hydrothermal addition, its heat resistance is significantly improved, which greatly expands the application range of polyimide.
[0012] As a preferred technical solution, the method for preparing the polyamic acid solution comprises the following steps: 1) Weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of organic solvent, stir and continuously introduce nitrogen; 2) Weigh 0.32 g to 1.55 g of rice-like hafnium dioxide nanoparticles, add them to the solution obtained in step 1) under stirring and continuous nitrogen flow until they are evenly dispersed to obtain a mixed solution; 3) Weigh 5.35 g of m-phenylenediamine, add it to the mixed solution obtained in step 2) under stirring and continuous nitrogen flow, and after uniform dispersion, place the obtained mixed solution at 50-80° C. for reaction for 4-12 hours, and cool to room temperature to obtain the product.
[0013] As a preferred technical solution, the organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0014] Another aspect of the present invention provides a method for preparing a polyimide enameled wire, comprising the following steps: 1) Preparation of rice-like hafnium dioxide nanoparticles: 3.22 g of HfCl4 was weighed and dissolved in 5 ml of methanol to obtain solution A; 1.51 g of CH3COONa was weighed and added to 10 ml of methanol to obtain solution B; solution B was added dropwise to solution A to obtain a mixed solution; the mixed solution was poured into a 50 ml autoclave, heated to 120°C~200°C and maintained at this temperature for 3~10 h, then the autoclave was cooled naturally, the product was collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h; 2) Prepare a polyamic acid solution: weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of an organic solvent, stir and continuously introduce nitrogen; weigh 0.32 g to 1.55 g of rice-like hafnium dioxide nanoparticles, add them to the solution obtained in the previous step under stirring and continuous introduction of nitrogen until they are evenly dispersed to obtain a mixed solution; weigh 5.35 g of m-phenylenediamine, add it to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after evenly dispersing, place the obtained mixed solution at 50 to 80° C. for reaction for 4 to 12 hours, and cool to room temperature; 3) Immersing the conductor into the polyamic acid solution obtained in step 2) for coating, and performing a multi-stage heating treatment until the surface of the conductor is coated with a polyimide coating of a desired thickness.
[0015] As a preferred technical solution, the conductor is a copper wire or an aluminum wire, the organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide, and the thickness of the polyimide coating is 0.01~0.1mm.
[0016] As a preferred technical solution, the step 3) is specifically as follows: placing the polyamic acid solution into a fixed container of a pulling coating machine, immersing the wire at a speed of 40 to 60 mm / min, and then lifting it at a speed of 10 to 30 mm / min for coating. The coated wire is placed in a tubular furnace and sequentially kept at 70 to 90°C for 2 to 4 hours, 140 to 160°C for 40 to 60 minutes, 220 to 240°C for 30 minutes to 40 minutes, and 280 to 300°C for 30 minutes to 40 minutes.
[0017] The present invention also provides an application of the polyimide enameled wire, wherein the polyimide enameled wire is wound into a winding coil for use in motor equipment, and the motor equipment using the winding coil can still work stably under long-term high temperature conditions.
[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: The present invention prepares rice-grain-shaped hafnium dioxide by a simple method. The nanoparticles are uniform in size and can be directly added to a polyimide precursor solution to prepare a polyimide coating. The nanoparticles are evenly dispersed in the polyimide coating without agglomeration. The present invention uses hafnium dioxide with a specific morphology to prepare a polyimide coating for the first time, which can effectively increase the initial decomposition temperature of the polyimide, and can increase the initial temperature of the polyimide coating from 448°C of pure polyimide and 471°C of the polyimide coating with spherical hafnium oxide added to 550°C, greatly expanding the use temperature range of the polyimide, improving the heat resistance of the enameled wire, and can be used stably for a long time at a higher temperature. At the same time, the hafnium dioxide nanoparticles themselves have a high dielectric constant and a low leakage rate, and can also improve the insulation performance of the enameled wire, enhance the mechanical strength of the coating, and improve the tensile and bending resistance of the enameled wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a cross-sectional SEM image of the enameled wire prepared in Comparative Example 1; Figure 2 The cross-sectional SEM and EDS spectra of the enameled wire prepared in Comparative Example 1 are shown; Figure 3 is a cross-sectional SEM image of the enameled wire prepared in Example 1; Figure 4 The cross-sectional SEM and EDS spectra of the enameled wire prepared in Example 1 are shown; Figure 5 is a SEM image of hafnium oxide nanoparticles prepared in Comparative Example 1; Figure 6 is a SEM image of rice-grain-shaped hafnium oxide nanoparticles prepared in Example 1; Figure 7 It is a comparison chart of the dielectric constants of the enameled wires prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0020] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0021] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0022] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0023] Example 1
[0024] A polyimide enameled wire comprises a conductor copper wire and a polyimide coating with a thickness of 0.01 mm arranged on the copper wire, wherein rice-grain-shaped hafnium dioxide nanoparticles are uniformly dispersed in the polyimide coating. The preparation method of the polyimide enameled wire comprises the following steps: 1) Preparation of rice-like hafnium dioxide nanoparticles: 3.22 g of HfCl4 was weighed and dissolved in 5 ml of methanol to obtain solution A; 1.51 g of CH3COONa was weighed and added to 10 ml of methanol to obtain solution B; solution B was added dropwise to solution A to obtain a mixed solution; the mixed solution was poured into a 50 ml autoclave, heated to 120°C and maintained at this temperature for 10 h, then the autoclave was cooled naturally, the product was collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h; 2) Prepare a polyamic acid solution: weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of N,N-dimethylformamide, stir and continuously introduce nitrogen; weigh 0.32 g of rice-like hafnium dioxide nanoparticles, add them to the solution obtained in the previous step under stirring and continuous introduction of nitrogen until they are evenly dispersed to obtain a mixed solution; weigh 5.35 g of m-phenylenediamine, add them to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after evenly dispersing, place the obtained mixed solution at 50°C for reaction for 4 hours and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the wire at a speed of 40mm / min, and then lift it at a speed of 10mm / min for coating. Put the coated wire into the tube furnace and keep it at 70℃ for 2h, 140℃ for 40min, 220℃ for 30min, and 280℃ for 30min. After testing, the average particle size of the hafnium dioxide nanoparticles is 140nm, the particles are rice-shaped, well dispersed, and evenly dispersed in the polyimide coating without agglomeration. The initial thermal decomposition temperature of the enameled wire is measured to be 531℃.
[0025] Example 2
[0026] A polyimide enameled wire comprises an aluminum conductor wire and a polyimide coating with a thickness of 0.1 mm disposed on the aluminum conductor wire, wherein rice-like hafnium dioxide nanoparticles are uniformly dispersed in the polyimide coating. The preparation method of the polyimide enameled wire comprises the following steps: 1) Preparation of rice-like hafnium dioxide nanoparticles: 3.22 g of HfCl4 was weighed and dissolved in 5 ml of methanol to obtain solution A; 1.51 g of CH3COONa was weighed and added to 10 ml of methanol to obtain solution B; solution B was added dropwise to solution A to obtain a mixed solution; the mixed solution was poured into a 50 ml autoclave, heated to 200°C and maintained at this temperature for 3 h, then the autoclave was allowed to cool naturally, the product was collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h; 2) Prepare a polyamic acid solution: weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of N-methylpyrrolidone, stir and continuously introduce nitrogen; weigh 1.55 g of rice-like hafnium dioxide nanoparticles, add them to the solution obtained in the previous step under stirring and continuous introduction of nitrogen until they are evenly dispersed to obtain a mixed solution; weigh 5.35 g of m-phenylenediamine, add them to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after evenly dispersing, place the obtained mixed solution at 80°C for reaction for 12 hours and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the wire at a speed of 60mm / min, and then lift it at a speed of 30mm / min for coating. Put the coated wire into the tube furnace and keep it at 90℃ for 4h, 160℃ for 60min, 240℃ for 40min, and 300℃ for 40min. After testing, the average particle size of the hafnium dioxide nanoparticles is 100nm, the particles are rice-shaped, well dispersed, and evenly dispersed in the polyimide coating without agglomeration. The initial thermal decomposition temperature of the enameled wire is measured to be 534℃.
[0027] Example 3
[0028] A polyimide enameled wire comprises a conductor copper wire and a polyimide coating with a thickness of 0.08 mm arranged on the copper wire, wherein rice-grain-shaped hafnium dioxide nanoparticles are uniformly dispersed in the polyimide coating. The preparation method of the polyimide enameled wire comprises the following steps: 1) Preparation of rice-like hafnium dioxide nanoparticles: 3.22 g of HfCl4 was weighed and dissolved in 5 ml of methanol to obtain solution A; 1.51 g of CH3COONa was weighed and added to 10 ml of methanol to obtain solution B; solution B was added dropwise to solution A to obtain a mixed solution; the mixed solution was poured into a 50 ml autoclave, heated to 150°C and maintained at this temperature for 5 h, then the autoclave was cooled naturally, the product was collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h; 2) Prepare a polyamic acid solution: weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of N,N-dimethylacetamide, stir and continuously introduce nitrogen; weigh 1.24 g of rice-like hafnium dioxide nanoparticles, add them to the solution obtained in the previous step under stirring and continuous introduction of nitrogen until they are evenly dispersed to obtain a mixed solution; weigh 5.35 g of m-phenylenediamine, add them to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after evenly dispersing, place the obtained mixed solution at 60°C for reaction for 5 hours and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the wire at a speed of 50mm / min, and then lift it at a speed of 20mm / min for coating. Put the coated wire into the tube furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 40min, and 300℃ for 40min. After testing, the average particle size of the hafnium dioxide nanoparticles is 116nm, the particles are rice-shaped, well dispersed, and evenly dispersed in the polyimide coating without agglomeration. The initial thermal decomposition temperature of the enameled wire is measured to be 533℃.
[0029] Example 4
[0030] A polyimide enameled wire comprises a conductor copper wire and a polyimide coating with a thickness of 0.05 mm arranged on the copper wire, wherein rice-grain-shaped hafnium dioxide nanoparticles are uniformly dispersed in the polyimide coating. The preparation method of the polyimide enameled wire comprises the following steps: 1) Preparation of rice-like hafnium dioxide nanoparticles: 3.22 g of HfCl4 was weighed and dissolved in 5 ml of methanol to obtain solution A; 1.51 g of CH3COONa was weighed and added to 10 ml of methanol to obtain solution B; solution B was added dropwise to solution A to obtain a mixed solution; the mixed solution was poured into a 50 ml autoclave, heated to 120°C and maintained at this temperature for 10 h, then the autoclave was cooled naturally, the product was collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h; 2) Prepare a polyamic acid solution: weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of dimethyl sulfoxide, stir and continuously introduce nitrogen; weigh 0.55 g of rice-like hafnium dioxide nanoparticles, add them to the solution obtained in the previous step under stirring and continuous introduction of nitrogen until they are evenly dispersed to obtain a mixed solution; weigh 5.35 g of m-phenylenediamine, add them to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after evenly dispersing, place the obtained mixed solution at 80°C for reaction for 10 hours and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the wire at a speed of 50mm / min, and then lift it at a speed of 20mm / min for coating. Put the coated wire into the tube furnace and keep it at 70℃ for 4h, 140℃ for 60min, 220℃ for 40min, and 280℃ for 40min. After testing, the average particle size of the hafnium dioxide nanoparticles is 150nm, the particles are rice-shaped, well dispersed, and evenly dispersed in the polyimide coating without agglomeration. The initial thermal decomposition temperature of the enameled wire is measured to be 534℃.
[0031] Comparative Example 1 A polyimide enameled wire comprises a copper wire and a polyimide coating with a thickness of 0.08 mm arranged on the copper wire, wherein spherical hafnium dioxide nanoparticles are uniformly dispersed in the polyimide coating. The preparation method of the polyimide enameled wire comprises the following steps: 1) Preparation of spherical hafnium dioxide nanoparticles: 3.22 g of HfCl4 was weighed and dissolved in 5 ml of methanol to obtain solution A; 2.4 g of NaOH was weighed and added to 20 ml of deionized water to obtain solution B; solution B was added dropwise to solution A with continuous stirring to obtain a mixed solution; the mixed solution was poured into a 50 ml autoclave, heated to 200°C and maintained at this temperature for 5 h, then the autoclave was cooled naturally, the product was collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h; 2) Prepare a polyamic acid solution: weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of N,N-dimethylacetamide, stir and continuously introduce nitrogen; weigh 1.24 g of spherical hafnium dioxide nanoparticles, add them to the solution obtained in the previous step under stirring and continuous introduction of nitrogen until they are evenly dispersed to obtain a mixed solution; weigh 5.35 g of m-phenylenediamine, add them to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after evenly dispersed, place the obtained mixed solution at 60°C for reaction for 5 hours and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the wire at a speed of 50mm / min, and then lift it at a speed of 20mm / min for coating. Put the coated wire into the tube furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 40min, and 300℃ for 40min. After testing, the average particle size of the hafnium dioxide nanoparticles is 350nm, the particles are spherical, with a certain degree of agglomeration, and the overall dispersion is uniform in the polyimide coating. Large particles or particle aggregation appear in some areas. The initial thermal decomposition temperature of the enameled wire is measured to be 482℃.
[0032] Comparative Example 2 A polyimide enameled wire comprises a copper wire and a polyimide coating with a thickness of 0.08 mm arranged on the copper wire. The preparation method of the polyimide enameled wire comprises the following steps: 1) Prepare a polyamic acid solution: weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of N,N-dimethylacetamide, stir and continuously introduce nitrogen; weigh 5.35 g of m-phenylenediamine, add it to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after uniform dispersion, place the obtained mixed solution at 60°C for reaction for 5 hours, and cool to room temperature; 2) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the wire at a speed of 50mm / min, and then lift it at a speed of 20mm / min for coating. Put the coated wire into the tubular furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 40min, and 300℃ for 40min. After testing, the initial thermal decomposition temperature of the enameled wire is 448℃.
[0033] Comparative Example 3 A polyimide enameled wire comprises a conductor copper wire and a polyimide coating with a thickness of 0.08 mm arranged on the copper wire, wherein hafnium dioxide nanoparticles are dispersed in the polyimide coating. The preparation method of the polyimide enameled wire comprises the following steps: 1) Preparation of rice-like hafnium dioxide nanoparticles: 3.22 g of HfCl4 was weighed and dissolved in 5 ml of methanol to obtain solution A; 0.51 g of CH3COONa was weighed and added to 10 ml of methanol to obtain solution B; solution B was added dropwise to solution A to obtain a mixed solution; the mixed solution was poured into a 50 ml autoclave, and 1 mL of deionized water was added, and it was heated to 150°C and maintained at this temperature for 5 h. After that, the autoclave was cooled naturally, the product was collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h; 2) Prepare polyamic acid solution: weigh 25.74g of pyromellitic anhydride and dissolve it in 150mL of N,N-dimethylacetamide, stir and continuously introduce nitrogen; weigh 2.1g of hafnium dioxide nanoparticles, add it to the solution obtained in the previous step under stirring and continuous introduction of nitrogen until it is evenly dispersed to obtain a mixed solution; weigh 7.15g of m-phenylenediamine, add it to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after it is evenly dispersed, place the obtained mixed solution at 60°C for reaction for 5h and cool to room temperature; 3) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the wire at a speed of 50mm / min, and then lift it at a speed of 20mm / min for coating. Put the coated wire into the tube furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 40min, and 300℃ for 40min. After testing, the size of the hafnium dioxide nanoparticles varies greatly, with a particle size distribution between 40nm and 130nm. The particles are mainly rice-shaped, with a small amount of spherical. They are not evenly dispersed in the polyimide coating and agglomerate in many places. The initial thermal decomposition temperature of the enameled wire is measured to be 459℃.
[0034] The enameled wires prepared in Example 1 and Comparative Example 1 were subjected to cross-sectional scanning and energy spectrum analysis. The results are shown in Figure 1~Figure 4 Compared with the SEM image of the cross-section of PI / spherical HfO2 enameled wire, the cross-section of PI / rice-grain-shaped HfO2 enameled wire shows that the nanoparticles are dispersed more evenly in the PI matrix, and there are no protrusions of the rice-grain-shaped HfO2 nanoparticles in the cross-section of the PI matrix, indicating that the special morphology of the rice-grain-shaped nanoparticles can be better dispersed in the PI matrix.
[0035] Figure 5 is a SEM image of spherical hafnium oxide nanoparticles prepared in Comparative Example 1. The spherical particles are roughly uniform, with large particles or particle aggregation in some areas; Figure 6 This is a SEM image of the rice-grain-like hafnium oxide nanoparticles prepared in Example 1. It can be seen from the figure that the prepared HfO2 nanopowder has a rice-grain-like morphology, is close in size, and the product is dispersed relatively evenly.
[0036] Figure 7It is a comparison chart of the dielectric constants of the enameled wires prepared in Example 1 and Comparative Examples 1 and 2. It can be seen from the figure that at 200 kHz, the dielectric constants of the corresponding materials of pure PI material, PI / HfO2 and PI / NaOAc-HfO2 (rice-grained) are 1.5, 4.2 and 4.3, respectively. The improvement of the dielectric constant of the composite material is mainly due to the high dielectric constant of the HfO2 nanoparticles themselves, and the HfO2 nanopowder with rice-grained morphology is uniformly dispersed in particle size, which is conducive to its effective dispersion in the PI matrix, thereby improving the stability of the dielectric properties of the PI composite material.
[0037] The above is a detailed introduction to a polyimide enameled wire and its preparation method. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. A polyimide enameled wire, comprising a conductor and a polyimide coating disposed on the conductor, characterized in that: Rice-grain-shaped hafnium dioxide nanoparticles are uniformly dispersed in the polyimide coating.
2. The polyimide enameled wire according to claim 1, characterized in that: The polyimide coating is formed by heating and curing a polyamic acid solution containing rice-grain-shaped hafnium dioxide nanoparticles.
3. The polyimide enameled wire according to claim 1, characterized in that: The average particle size of the hafnium dioxide nanoparticles is 100-150 nm, accounting for 1%-5% of the total weight of the polyimide coating.
4. The polyimide enameled wire according to claim 1, characterized in that: The conductor is a copper wire or an aluminum wire, and the thickness of the polyimide coating is 0.01-0.1 mm.
5. The polyimide enameled wire according to claim 1, characterized in that: The rice-grain-shaped hafnium dioxide nanoparticles are prepared by the following method: 3.22 g of HfCl4 is weighed and dissolved in 5 ml of methanol to obtain solution A; 1.51 g of CH3COONa is weighed and added to 10 ml of methanol to obtain solution B; solution B is added dropwise to solution A to obtain a mixed solution; the mixed solution is poured into a 50 ml high-pressure reactor, heated to 120°C~200°C and maintained at this temperature for 3~10 h, then, the high-pressure reactor is cooled naturally, the product is collected after centrifugal washing, and then placed in a forced air drying oven at 90°C for 5 h to obtain the product.
6. The polyimide enameled wire according to claim 2, characterized in that: The polyamic acid solution is prepared by the following method: Step 1: Weigh 25.74 g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150 mL of an organic solvent, stir and continuously introduce nitrogen; Step 2: Weigh 0.32 g to 1.55 g of rice-like hafnium dioxide nanoparticles, add them to the solution obtained in step 1 under stirring and continuous nitrogen flow until they are evenly dispersed to obtain a mixed solution; Step 3: Weigh 5.35 g of m-phenylenediamine, add it to the mixed solution obtained in step 2 under stirring and continuous nitrogen flow, and after uniform dispersion, place the obtained mixed solution at 50-80° C. for reaction for 4-12 hours, and cool to room temperature to obtain the product.
7. The polyimide enameled wire according to claim 6, characterized in that: The organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
8. A method for preparing a polyimide enameled wire according to any one of claims 1 to 7, characterized in that: The steps include: Step 1, preparation of rice-like hafnium dioxide nanoparticles: weigh 3.22 g of HfCl4 and dissolve it in 5 ml of methanol to obtain solution A; weigh 1.51 g of CH3COONa and add it to 10 ml of methanol to obtain solution B; add solution B dropwise into solution A to obtain a mixed solution; pour the mixed solution into a 50 ml autoclave, heat it to 120°C~200°C and keep it at this temperature for 3~10 h, then wait for the autoclave to cool naturally, collect the product after centrifugal washing, and then place it in a forced air drying oven at 90°C for 5 h; Step 2, prepare a polyamic acid solution: weigh 25.74g of 4,4'-isopropyldiphenoxy-diphthalic anhydride and dissolve it in 150mL of an organic solvent, stir and continuously introduce nitrogen; weigh 0.32g~1.55g of rice-shaped hafnium dioxide nanoparticles, add them to the obtained organic solution dissolved with 4,4'-isopropyldiphenoxy-diphthalic anhydride under stirring and continuous introduction of nitrogen until it is evenly dispersed to obtain a mixed solution; weigh 5.35g of m-phenylenediamine, add it to the obtained mixed solution under stirring and continuous introduction of nitrogen, and after uniform dispersion, place the obtained mixed solution at 50~80°C for reaction for 4~12h, and cool to room temperature; Step 3: Immerse the conductor in the polyamic acid solution obtained in step 2 for coating, and perform multi-stage heating treatment until the surface of the conductor is coated with a polyimide coating of a desired thickness.
9. The method for preparing a polyimide enameled wire according to claim 8, characterized in that: The conductor is a copper wire or an aluminum wire, the organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide, and the thickness of the polyimide coating is 0.01-0.1 mm.
10. The method for preparing a polyimide enameled wire according to claim 8, characterized in that: The step three is specifically as follows: placing the polyamic acid solution into a fixed container of the pulling coating machine, immersing the wire at a speed of 40 to 60 mm / min, and then lifting it at a speed of 10 to 30 mm / min for coating, placing the coated wire into a tubular furnace, and sequentially keeping it at 70 to 90° C. for 2 to 4 hours, keeping it at 140 to 160° C. for 40 to 60 minutes, keeping it at 220 to 240° C. for 30 minutes to 40 minutes, and keeping it at 280 to 300° C. for 30 minutes to 40 minutes.
Citation Information
Patent Citations
Polyamide acid dispersion liquid and preparation method thereof as well as polyimide film
CN103172859A
Preparation method of high-elasticity and high-heat-resistance polyimide
CN111154100A
Polyimide dielectric film and preparation method and application thereof
CN111234529A
Preparation method of high-temperature-resistant polyimide enamelled wire enamel
CN112592653A
Polyimide paint for high-heat-resistance enameled wire and high-heat-resistance enameled wire
CN115746696A
Cited By
High-pressure-resistant corrosion-resistant nano-composite coating material for tank body of oil tank truck and preparation method thereof
CN121851883A